Gender differences in the knee adduction moment after anterior cruciate ligament reconstruction surgery. Issue 5 (20th April 2011) - Webster, Kate E; McClelland, Jodie A; Palazzolo, Simon E; Santamaria, Luke J; Feller, Julian A
Abstract : Background: The external knee adduction moment during gait has previously been associated with knee pain and osteoarthritis (OA). Recently, the knee adduction moment has been shown to be increased following anterior cruciate ligament (ACL) reconstruction surgery and has been suggested as a potential mechanism for the progression of early onset knee OA in this population. No study has investigated the gender differences in gait biomechanics following ACL reconstruction. Aim: To examine gender differences in gait biomechanics following ACL reconstruction surgery. Methods: 36 subjects (18 females, 18 males) who had previously undergone ACL reconstruction surgery (mean time since surgery 20 months) underwent gait analysis at a self-selected walking speed. Males and females were well matched for age, time since surgery and walking speed. Maximum flexion and adduction angles and moments were recorded during the stance phase of level walking and compared between the male and female groups. Results: The knee adduction moment was 23% greater in the female compared with the male ACL group. No gender differences were seen in the sagittal plane. No differences were seen between the reconstructed and contralateral limb. Conclusion: The higher knee adduction moment seen in females compared with males may suggest an increased risk for the development of OA in ACL-reconstructed females.